Framework of conceptual design methodology for hybrid buoyant aircraft - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Mohamed Ali, Jaffar Syed (Associazione Italiana di Aeronautica e Astronautica, Sede di Pisa, 2016)
For economic and `green' transportation, the concept of hybrid buoyant aircraft has recently become a research focus in the aerospace community. In the present work, a methodology is proposed to aid in the conceptual design of such aircraft, powered by internal combustion engines with either liquid hydrogen or gasoline as a fuel. Special emphasis is given to the sequence of procedures to be adopted at the conceptual design level highlighting a step by step methodology for the achievement of system design targets with the help of a design example. The proposed design synthesis methodology has given a base line for further design work on such aircraft at a conceptual level. Moreover, it will assist to provide qualitative as well as quantitative data for other design concepts of such hybrid configurations being considered in the conceptual design phase.